THE EFFECT OF CAREER DEVELOPMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN PT JABAR JAYA PERKASA - Nita Tri Febrianti; Suharto; Wachyudi (The Institute of Academic Research and Publication (IARP), 2020)
This study aims to: 1) To find out and analyze the effect of career development and motivation on job satisfaction, 2) To know and analyze the effect of career development and motivation on employee performance, 3) To find out and analyze the effect of job satisfaction on employee performance, 4) To find out and analyze the influence of career development and motivation on employee performance through job satisfaction PT. Jabar Jaya Perkasa. The study was conducted at PT. Jabar Jaya Perkasa with a research sample of 58 respondents. The sampling technique uses saturated samples. The data analysis method uses descriptive analysis and quantitative analysis with path analysis. The results showed that: 1) there was an influence on career development and motivation on job satisfaction, 2) there was an influence on career development and motivation on employee performance, 3) there was an effect on job satisfaction on employee performance and 4) there was no influence on career development and motivation on performance employees through job satisfaction PT. Jabar Jaya Perkasa. This means that the direct effect is greater than the indirect effect, the variable job satisfaction cannot mediate between motivation and job satisfaction on employee performance at PT. Jabar Jaya Perkasa.